A Rare Case of a Renal Cell Carcinoma Confined to the Isthmus of a Horseshoe Kidney - Michael Kongnyuy; Daniel Martinez; Anthony Park; Barrett McCormick; Justin Parker; Mary Hall (Case Reports in Urology)
Horseshoe kidney (HSK) is the most common renal anomaly. Reports of the incidence of renal cell carcinoma (RCC) in HSK are conflicting. Very few cases of isthmus-located RCC have been reported in the literature. We report a unique case of an isthmus-located RCC. Proper vascular and tumor imaging prior to surgery is key to successful tumor removal.